Knowledge-based changes to health systems: the Thai experience in policy development - Viroj Tangcharoensathien; Suwit Wibulpholprasert; Sanguan Nitayaramphong (The World Health Organization, 2004)
Over the past two decades the government in Thailand has adopted an incremental approach to extending health-care coverage to the population. It first offered coverage to government employees and their dependants, and then introduced a scheme under which low-income people were exempt from charges for health care. This scheme was later extended to include elderly people, children younger than 12 years of age and disabled people. A voluntary public insurance scheme was implemented to cover those who could afford to pay for their own care. Private sector employees were covered by the Social Health Insurance scheme, which was implemented in 1991. Despite these efforts, 30% of the population remained uninsured in 2001. In October of that year, the new government decided to embark on a programme to provide universal health-care coverage. This paper describes how research into health systems and health policy contributed to the move towards universal coverage. Data on health systems financing and functioning had been gathered before and after the founding of the Health Systems Research Institute in early 1990. In 1991, a contract capitation model had been used to launch the Social Health Insurance scheme. The advantages of using a capitation model are that it contains costs and provides an acceptable quality of service as opposed to the cost escalation and inefficiency that occur under fee-for-service reimbursement models, such as the one used to provide medical benefits to civil servants. An analysis of the implementation of universal coverage found that politics moved universal coverage onto the policy agenda during the general election campaign in January 2001. The capacity for research on health systems and policy to generate evidence guided the development of the policy and the design of the system at a later stage. Because the reformists who sought to bring about universal coverage (who were mostly civil servants in the Ministry of Public Health and members of nongovernmental organizations) were able to bridge the gap between researchers and politicians, an evidence-based political decision was made. Additionally, the media played a part in shaping the societal consensus on universal coverage.